Pengaruh Motivasi Orang Tua Terhadap Prestasi Belajar Pendidikan Agama Islam Siswa Madrasah Tsanawiyah Tahfidzul Quran Al-Fatah Sambi Kabupaten Boyolali - Bangun Ariyanto; Ngatmin Abbas; M. Yunan Hidayat (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
This study examined parental motivation and Islamic Religious Education achievement among ninth-grade students at Tahfidzul Qur’an Al-Fatah Islamic Junior High School in Sambi, Boyolali. It also investigated whether parental motivation was significantly associated with students’ academic achievement. The study employed a quantitative approach with a correlational design. The population consisted of 28 students, all of whom were selected through total sampling. Data on parental motivation were collected using a 30-item questionnaire, while academic achievement data were obtained from school records. The data were analyzed using descriptive statistics, validity and reliability tests, normality and linearity tests, and simple linear regression. The results showed that parental motivation was in the moderate category, with a mean score of 130.54. Of the respondents, 67.9% reported moderate parental motivation, 17.9% high motivation, and 14.3% low motivation. Students’ academic achievement was also classified as moderate, with a mean score of 687.04. A total of 60.7% of students were in the moderate category, 21.4% in the high category, and 17.9% in the low category. The regression analysis produced a correlation coefficient of 0.268 and a coefficient of determination of approximately 7.2%. The model yielded an F-value of 2.010 with a significance level of 0.168. These findings indicate a weak positive relationship between parental motivation and academic achievement, but the relationship was not statistically significant. Students’ achievement may also be shaped by individual, pedagogical, social, and institutional factors.